Modelling the energy extraction from low-velocity stream water by small scale Archimedes screw turbine - Lee, Man Djun; Lee, P.S. (2021)
In recent years, there has been a growth of interest in the development of micro-hydropower power generation, especially in the low head turbine. Low head turbine gained popularity due to its high efficiency, relatively low cost, ability to operate in low flow rate, and low environmental impact. In this aspect, the Archimedes Screw Turbine (AST) could be the primary key to electrifying the rural area in Sarawak, Malaysia, which is surrounded by rivers. This study starts with a conceptual design based on literature review findings. Eventually, the small-scale prototype is then being built and tested in the laboratory. The experiment is set up to simulate the actual Sarawak river velocity to determine the relationship between key performance variables such as the inclination angle of AST and water flow velocity. The findings revealed that the 45° angle of inclination was the optimum angle of AST within the water velocity of 1.0 m/s until 1.5 m/s. At this angle, the highest revolution per minute (RPM) generated by AST shaft was 179.8, and the highest torque recorded was 0.9Nm. The results were validated through statistical means. It was found that both angle of inclination and river water velocity are significant to RPM and torque generation (p < 0.05). Two statistical models were generated based on linear regression to explain the contribution of water velocity and angle of inclination as inputs to torque and RPM as outputs, with Pearson R2 value of more than 60%. The maximum mechanical power generated is about 1.54 kW, with the maximum efficiency of 94.6%. The outcome of this study would be useful for designing a small-scale AST power generation system by utilising a low flow river (velocity < 1.5 m/s) as a power source. This study would contribute to the existing knowledge stock of small-scale AST, primarily to operate in low flow velocity rivers. For the future study, it is recommended for conducting a pilot study to test the actual performance of AST in the Sarawak river or rivers with similar flow characteristics.